Global tensions : challenges and opportunities in the world economy - Benería, Lourdes; Bisnath, Savitri, 1965- (Routledge, 2004)
Composed of original essays by renowned scholars, this volume explores controversial topics such as free trade, women's rights, labor standards, the World Trade Organization and global tensions.
Keywords: Free trade.; Foreign trade and employment.; Globalization -- Economic aspects.; Globalization -- Social aspects.; Anti-globalization movement.; International economic relations.; Libre-échange.; Commerce international et emploi.; Mondialisation.; Mondialisation -- Aspect social.; Altermondialisme.; globalism.; BUSINESS & ECONOMICS -- International -- General.; BUSINESS & ECONOMICS -- International -- Economics.; Anti-globalization movement; Foreign trade and employment; Free trade; Globalization -- Economic aspects; Globalization -- Social aspects; International economic relations; Multi-User: limited to 5 simultaneous users.